Policy of welfare state as the state’s responsibility for society – a global view - Rubaj, Piotr (Polityka państwa dobrobytu jako odpowiedzialność państwa za społeczeństwo – ujęcie globalne, 2016)
In the second part of the 20th century “welfare state” model became a recognizable part of social-economic policy in majority of Western countries, called west civilisation countries. Remarkable achievements of this model like: generous social care programs, free education and healthcare systems, complex and universal state support for the families, supplementary payments for them and egalitarian way of income distribution distinguish it from other countries and civilisations. For many years this model was recognized as undoubted achievement of Western civilisation. However, changes in the global economy at the turn of 20th and 21st centuries influenced the “welfare state” policy, which started to be interpreted as a barrier in economic growth. Nowadays, for many people it seems to be a kind of dilemma either to choose dynamic economic growth or rich social state contribution to its society.
Społeczeństwo i Ekonomia = Society and Economics, 2016, Nr 1 (5), s. 98-107
Keywords: welfare state policy; social policy; welfare systems; polityka państwa dobrobytu; polityka welfare state; polityka społeczna